The Critical Path (American Journal of Islam and Society, 2000)
Contemporary Islamic scholarship emerged in the mid-nineteenth centuryin response to the overall stagnation of Muslim society and culture.Muslim reformers advanced a simple but powerful thesis: overcoming theweaknesses and deficiencies of contemporary Muslim society requires profoundsocial and cultural reforms, and hence a critical examination of traditionalthought and institutions.The pioneers of contemporary Islamic reform were versed in both modemWestern and traditional Islamic thought. Early reformers, such as Al-Afghani, Abduh, al-Kawakibi, and Iqbal critically engaged both the systemof ideas inherited from the Muslim past and those received from the modernWest. Their free spirit, inquisitive minds, and unyielding courageallowed them to place intellectual reform on a critical yet balanced path.While the tradition of critical thinking they espoused continues to growand flourish among many contemporary Muslim thinkers, the balance theymaintained in criticizing the self and the other has been lost by a large segmentof Muslim intellectuals. Most Muslim intellectuals are critical ofeither traditional Muslim scholarship or Western thought, but seldom both.This one-sidedness has turned knowledge and scholarship into a partisantool to be used against the perceived ideological adversary.Factors contributing to the one-sidedness of many contemporary Muslimscholars are numerous, and are often rooted in pure political or economicmotives. Two factors, however, stand out as expressively theoretical andintellectual: the ahistorical view of ideas and concepts among Muslims,whereby what has been devised by early scholars is given universal andabsolute validity; and the absence of an Archimedean point from which theintellectual can judge both.For over a century now, Muslim intellectuals have been divided into twomajor blocs, the advocates of modernity and the defenders of Islamic tradition.The former continue to see Islam as a premodern legacy, incapable ofleading Muslim society into a challenging future. Trapped in an end-of-historymindset, they have not been able to develop a critical approach to ...